2019
DOI: 10.3390/s19061282
|View full text |Cite
|
Sign up to set email alerts
|

Assisting Visually Impaired People in the Public Transport System through RF-Communication and Embedded Systems †

Abstract: For a significant number of people with visual impairments, public transport plays an important role in productivity, community participation, and independence, since it may be the only feasible mobility option to participate in their education, work, medical care, food, and to attend many other places in their community. To use the public bus system safely, effectively, and autonomously, these people need to collect information about their physical environment and visible information at stops and terminals, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Formula (19) can be converted into Formula (20), and the relationship between Formulas (1) and (20) can be presented by Formula 21:…”
Section: Transportation Utility Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formula (19) can be converted into Formula (20), and the relationship between Formulas (1) and (20) can be presented by Formula 21:…”
Section: Transportation Utility Methodsmentioning
confidence: 99%
“…[19] proposed a method based on running timetables and position coordinates to analyze the vulnerabilities and critical areas of PT systems in China and indicated that economic development and population density are essential to PT system design. Saez et al (2019) [20] proposed an assistance system based on radio frequency communication technologies for people with visual disabilities to facilitate their mobility in PT systems. Perera et al (2020) [21] designed a lifecycle thinking-based multi-period PT infrastructure-planning framework to develop sustainable electric vehicles.…”
Section: Public Transportationmentioning
confidence: 99%
“…Route selection consists of pedestrian routing and public transportation as sub-tasks (read Section 7.4 ). Public transportation as part of journey planning does not appear in the literature [ 32 , 78 , 79 ] therefore, the focus of this section is on pedestrian routing. This problem of route selection problem is a significant task for navigation of vehicles [ 123 ] or pedestrians with and without disabilities [ 122 ].…”
Section: Journey Planningmentioning
confidence: 99%
“…Each step on this task merits consideration in any study to determine the needs of BVIP across multiple contexts. For instance, ’ Finding the correct service’ step at the bus stop is about catching the right bus for the destination [ 32 , 66 , 78 , 79 ] when it arrive at a bus stop. In contrast, this step is more complicated in the airport [ 159 ] or large scale train station [ 114 ].…”
Section: Real-time Navigationmentioning
confidence: 99%
“…In the first paper, “Assisting Visually Impaired People in the Public Transport System through RF-Communication and Embedded Systems” [3], a new approach is described to provide autonomous mobility in the public transport system to visually impaired persons by means of radio frequency communication and embedded systems. The main advantages of this new proposal are that it is low cost, user-friendly, modular, and requires no audio cues, which make it a good alternative to the current approaches.…”
mentioning
confidence: 99%